Evidence for ultrafast formation of tribenzoylgermyl radicals originating from tetraacylgermane photoinitiators. Issue 24 (8th June 2020) - Jöckle, Philipp; Lamparth, Iris; Moszner, Norbert; Barner-Kowollik, Christopher; Unterreiner, Andreas-Neil
Abstract : We report strong evidence for the ultrafast formation of tribenzoylgermyl radicals originating from tetraacylgermane photoinitiators on a ps-time scale. In comparison to previous studies, the result can be related to a high initiation efficiency. Abstract : Mono-, bis-, and tetraacylgermane derivatives are promising photoinitiators for visible light-induced free radical polymerization. In the current study, the ultrafast dynamics of one unsubstituted as well as two ortho -methyl- and -ethyl-substituted tetraacylgermane derivatives were investigated in solution at ambient temperature via femtosecond-transient broadband (350–680 nm) absorption spectroscopy after 400 nm excitation. For the first time, we provide evidence for an initial formation of tribenzoylgermyl radical fragments originating from tetraacylgermane derivatives within 90–127 ps. By comparison to our previous quantitative pulsed laser polymerization and mass spectrometry study, the ultrafast radical formation can be related to the most efficient initiation ability compared to mono- and bis-derivatives.